2021
DOI: 10.31557/apjcp.2021.22.9.2879
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Zinc Supplement in Minimal hepatic Encephalopathy: A prospective, Randomized Controlled Study (Zinc-MHE Trial)

Abstract: Background: Minimal hepatic encephalopathy (MHE) in patients with cirrhosis of the liver has a negative impact on the quality of daily life by impairing attention, memory and visuomotor coordination, and resulting in cognitive decline. Ammonia is thought to be part of the pathogenesis of hepatic encephalopathy. Zinc is an essential trace element, one of the cofactor enzymes that is essential for the conversion of ammonia to urea. Aim: To assess the effect of zinc supplementation on psychomotor performance in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, zinc—a microelement crucial for our immune system homeostasis—is also a cofactor for ammonia conversion to urea. Thus, zinc deficiency is strictly linked to hepatic encephalopathy [ 50 ]. Conversely, patients with ALF derived from undiagnosed Wilson disease can present with copper-driven toxicity [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, zinc—a microelement crucial for our immune system homeostasis—is also a cofactor for ammonia conversion to urea. Thus, zinc deficiency is strictly linked to hepatic encephalopathy [ 50 ]. Conversely, patients with ALF derived from undiagnosed Wilson disease can present with copper-driven toxicity [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zinc has been proposed as a potential treatment option for HE given its mechanism of action in cirrhosis and the urea cycle, and prior studies have shown potential benefit. [5][6][7][8] However, the outcomes from prior studies were improvement in NP test results, changes in ammonia levels, and healthcare quality of life scores, and none evaluated the effects of zinc on readmission rates nor were conducted in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Prior studies have evaluated zinc therapy for HE treatment, but they had various comparator groups and outcomes (Table 1). [5][6][7][8] Zinc was compared to the following: placebo, BCAAs, lactulose, and various international standard HE therapies (protein-restricted diet with lactulose, protein-restricted diet with BCAAs and lactulose), but none of the prior studies included patients on rifaximin. Therefore, these studies are not applicable to the management of HE in patients with cirrhosis already on lactulose and rifaximin.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on zinc supplementation in cirrhosis focused on its effects on hepatic encephalopathy. Despite the fact that some authors demonstrated an improvement in amino acids metabolism and hepatic encephalopathy [233][234][235][236][237], while a few studies reported a better prognosis due to lower frequency of liver decompensation and HCC development in cirrhotic patients with low zinc serum levels treated with supplementation [238,239], there is still no consensus on the dose and timing of supplementation. A particular case is represented by chronic alcohol intoxication, where low levels of brain zinc have been associated with an increased sensitivity to alcohol withdrawalinduced seizures, and zinc supplementation may alleviate general alcohol withdrawal symptoms [240].…”
Section: Zincmentioning
confidence: 99%